DESIGN OF MOVEMENT SYSTEM SHAKER SCREEN SEATHER MACHINE Crankshaft ROTATION - Rahman Pebrian A R; Asep Rachmat; Nasim nasim (Universitas Majalengka, 2022)
The sand sieving machine, shaker screen, crankshaft rotational motion system, is a machine that facilitates building work in separating the mixture of sand and gravel. In the design and analysis related to the selection of the frame model in order to determine the strength of the material in holding each component of the sand sieving machine, this research uses solidwork software, based on the results of the solidwork software simulation, the stress value in the sieving tank is 3,303 N/mm2, the displacement value is 2,325 mm, the safety factor by means of a simulation of 4,059. The capacity of the shaker screen sand sieving machine has a volume of 0.824 with a length of 160 cm, a width of 70 cm and a capacity of accommodate wet and dry sand media weighing 30 kg.